The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1130/ges01410.1
|View full text |Cite
|
Sign up to set email alerts
|

Detrital-zircon records of Cenomanian, Paleocene, and Oligocene Gulf of Mexico drainage integration and sediment routing: Implications for scales of basin-floor fans

Abstract: This paper uses detrital zircon (DZ) provenance and geochronological data to reconstruct paleodrainage areas and lengths for sediment-routing systems that fed the Cenomanian Tuscaloosa-Woodbine, Paleocene Wilcox, and Oligo cene Vicksburg-Frio clastic wedges of the northern Gulf of Mexico (GoM) margin. During the Cenomanian, an ancestral Tennessee-Alabama River system with a distinctive Appalachian DZ signature was the largest system contributing water and sediment to the GoM, with a series of smaller systems d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(144 citation statements)
references
References 108 publications
12
130
2
Order By: Relevance
“…Calculated Cenozoic discharge suggests that the major continental-scale catchments (e.g., Mississippi, Colorado, Columbia, Yukon, and Mackenzie) are broadly stable. For example, most of the large rivers that drain western North America into the Gulf of Mexico have similar flow patterns over the last ∼65 Ma, which is consistent with zircon provenance measurements from Cretaceous and Paleocene fluvial sandstones along the northern margin of the Gulf of Mexico (Figure 2; Blum & Pecha, 2014;Blum et al, 2017). Similar results have been obtained for the random slope condition and for the 1% initial condition.…”
Section: Calculated Landscapesupporting
confidence: 84%
See 4 more Smart Citations
“…Calculated Cenozoic discharge suggests that the major continental-scale catchments (e.g., Mississippi, Colorado, Columbia, Yukon, and Mackenzie) are broadly stable. For example, most of the large rivers that drain western North America into the Gulf of Mexico have similar flow patterns over the last ∼65 Ma, which is consistent with zircon provenance measurements from Cretaceous and Paleocene fluvial sandstones along the northern margin of the Gulf of Mexico (Figure 2; Blum & Pecha, 2014;Blum et al, 2017). Similar results have been obtained for the random slope condition and for the 1% initial condition.…”
Section: Calculated Landscapesupporting
confidence: 84%
“…Timing of these depositional phases is broadly coeval with the history of uplift estimated from clumped isotopes (Δ 47 ) and with other paleoaltimetric proxies, which imply that the Colorado Plateau had an elevation of 1-2 km between Cretaceous and Oligocene times (e.g., Gregory & Chase, 1992;Huntington et al, 2010;Wolfe et al, 1998). Galloway et al (2011), Blum and Pecha (2014), and Blum et al (2017) argue that large-scale drainage of the Cordilleran highlands toward the Gulf of Mexico existed by at least Late Paleocene times and that drainage catchments probably extended up to the western flank of the Appalachian mountains. Further west, Cather et al (2008) identified a major denudation event within the Colorado Plateau between the deposition of the Chuska Erg (35-27 Ma) and the Bidahochi Formation (∼16 Ma).…”
Section: Post-cretaceous Eventsmentioning
confidence: 81%
See 3 more Smart Citations